Medicament for inhibiting cancer cells without harmful effect to normal cells - CHEN LEZONG; CHEN HAO; ZHANG JIETING; ZHAO WENCHAO; LIN XIAOLI; LI MING; CHENG LEI (2010)
The present invention relates to a pharmaceutical composition and a method for treating cancer, especially relates to a pharmaceutical composition including curative dose plant extract and pharmaceutically acceptable carrier and a method for treating cancer by using same.